John Vorster and the Extension of University Education Act, 1959 (Historia, 2023)
In February 1959, four months after his appointment as deputy minister, Balthazar Johannes (John) Vorster introduced the controversial Extension of University Education Bill in the House of Assembly. University apartheid had been under consideration in the National Party government for more than a decade. The 1959 bill provided for the exclusion of ‘non-European’ students from the existing universities and their admission to separate university colleges for the different officially designated ethnic groups. Liberals rejected the bill as a threat to academic freedom and university autonomy. The Opposition opposed the bill in all its parliamentary stages. This article analyses Vorster's performance in these debates. It was a severe test for his ability, but he demonstrated his talent as speaker and debater, confidently formulating his arguments in favour of the bill and standing his ground against the Opposition. The parliamentary newspaper reporters were impressed by his contribution to the debates. Vorster's leadership position in the National Party was strengthened. The debates provided an early stepping-stone in his political career, that launched him on his way to becoming Minister of Justice, prime minister, and state president.